1989
DOI: 10.1177/002204268901900304
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Small Town Physicians and Their Spouses

Abstract: Based on the results of a self-administered questionnaire completed by 107 wives of physicians in a rural central California county, this exploratory study examines dimensions of the physician's work and family life associated with excessive use of alcohol. Avoiding the bias of the use of a treatment population, the study seeks to analyze the factors that are predictive of alcohol impairment in physicians' living and practicing in rural areas where role strain is increased. The stress theory's role in explaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
1998
1998

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…For example, studies have shown that occupational or workplace stress is associated with depression (Revicki & May, 1983), free-floating anxiety (Green, Duthie, Young, & Peters, 1990), somatic anxiety (Sutherland & Cooper, 1992), burnout and suicidal thoughts (Olkinuora et al, 1990), distress (King, Cockcroft, & Gooch, 1992), emotional exhaustion (Deckard et al, 1994), excessive use of alcohol (Estep, Novack, & Helsel, 1989), suicide and substance abuse (cited by King et al, 1992), and low job satisfaction (Cooper, Rout, & Faragher, 1989). …”
Section: Introductionmentioning
confidence: 99%
“…For example, studies have shown that occupational or workplace stress is associated with depression (Revicki & May, 1983), free-floating anxiety (Green, Duthie, Young, & Peters, 1990), somatic anxiety (Sutherland & Cooper, 1992), burnout and suicidal thoughts (Olkinuora et al, 1990), distress (King, Cockcroft, & Gooch, 1992), emotional exhaustion (Deckard et al, 1994), excessive use of alcohol (Estep, Novack, & Helsel, 1989), suicide and substance abuse (cited by King et al, 1992), and low job satisfaction (Cooper, Rout, & Faragher, 1989). …”
Section: Introductionmentioning
confidence: 99%